Carbon and nitrogen inputs differentially affect priming of soil organic matter in tropical lowland and montane soils. (February 2019) - Hicks, Lettice C.; Meir, Patrick; Nottingham, Andrew T.; Reay, Dave S.; Stott, Andrew W.; Salinas, Norma; Whitaker, Jeanette
Abstract: Microbial decomposition of soil organic matter (SOM) can be accelerated or reduced by the combined effects of carbon (C) and nutrient inputs through a phenomenon known as 'priming'. Tropical lowland and montane soils contain large stores of C and may undergo substantial future changes in C and nutrient inputs due to global change, yet how these inputs might interact to influence priming is poorly understood in these ecosystems. We addressed this question using soils from a 3400 m tropical elevation gradient which vary strongly in nitrogen (N) and phosphorus (P) availability. To determine how existing nutrient availability in different tropical soils regulates microbial activity, and whether microbial demand for nutrients leads to priming, soils were amended with simple and more complex 13 C-labelled substrates in combination with inorganic N, P and N + P. Isotopic partitioning ( 13 C in CO2 and in phospholipid fatty acids; PLFA) was used to identify sources of C (substrate- or SOM-derived) in respiration and in microbial communities. Nutrient treatments did not influence the amount of substrate-respired C for any of the soils, but did affect the direction and magnitude of priming effects. For the upper montane forest and grassland soils, C addition had a relatively minor influence on the turnover of SOM, but N addition (with or without C) reduced SOM mineralisation (negative priming), suggesting reduced microbial N-mining from SOM when N was externally supplied. By contrast, in the lower montane and lowland forest soils, C addition increased SOM mineralisation (positive priming), but the response was unaffected by nutrient additions. The assimilation of 13 C substrates into functionally active microorganisms revealed that C substrate complexity, but not added nutrients, strongly affected C-use within the microbial community: in both lowland and montane forest soils, fungi assimilated a greater proportion of the simple C substrate, while gram-positive bacteria assimilated a greater proportion of the more complex C substrate. Overall, our results have contrasting implications for the response of soil C cycling in tropical montane and lowland ecosystems under future global change. Highlights: Tropical soils were amended with carbon substrates and inorganic nutrients. Nutrient treatments did not influence the mineralisation of added C substrates. Nitrogen addition reduced SOM mineralisation in higher elevation montane soils. Neither nitrogen or phosphorus influenced SOM mineralisation in lowland soils. C substrate complexity strongly affected C-use within the microbial community.